KECERDASAN KOLEKTIF PETANI DI LAHAN PERTANIAN PASIR PANTAI KECAMATAN PANJATAN KABUPATEN KULON PROGO - Siwi Istiana Dinarti; Sri Peni Wastutiningsih; Subejo Subejo; Supriyanto Supriyanto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2013)
This study aims to determine the process of collective intelligence of farmers to describe level of collective intelligence of farmers in coastal agriculture area farm management and factors of the collective intelligence of farmers. in coastal agriculture area. The basic method used here was namely analytical descriptive method. The sample was taken with purposive method. Analysis method was done by using chi-square and gamma tests. The results showed that the process as of collective intelligence of coastal agriculture area fanners in Panjatan Sub District were social learning and consensus process. Level of collective intelligence of farmers' on the coastal agriculture area tends to be high. Indicators of collective intelligence that have been done by all of the farmers were land clearing for agriculture, land consolidation, farm road construction, group planning arrangement, auction markets arrangement, and pantek well construction. There were two indicators which haven't been done by farmers i.e. using of plastic mulch a.nd using of power sprayer. The factors affecting collective intelligence are farmer's organization activities, farmer's experience and land size.